What attitudes do young men in Cape Town hold towards gender-based violence movements? - Rumblelow, Rachael (The IIE, 2020)
This study aimed to identify and understand the attitudes young men in Cape Town have regarding GBV movements. Gender based violence (GBV) is an issue which 30% of all women over 15 years old have experienced. This rate increases dramatically in the context of South Africa. As feminism has evolved, the inclusion of men in GBV movements has been introduced. However, the rate of male participation in GBV movements remains low. This study aimed to determine the perceptions and behaviours young men in Cape Town have towards GBV movements so as to learn why their rate of involvement is low, as well as to determine how the movements have influenced this rate. A group of young men from Cape Town were involved in a focus group to allow for an open discussion consisting of specific answers surrounding GBV and GBV movements. From this, the transcripts were analysed from an interpretative phenomenological framework. It was found that the men had negative attitudes towards GBV. It was decided that the men’s attitudes toward GBV is not entirely shaped by their attitudes towards GBV movements. This is because it was found that their attitudes towards GBV movements are undetermined as they each discussed positive and negative perceptions and behaviours towards the movements.
Keywords: Attitudes of men; Gender-based violence (GBV); GBV movements